The locus of impairment in English developmental letter position dyslexia - Kezilas, Yvette; Kohnen, Saskia; McKague, Meredith; Castles, Anne (Frontiers in Human Neuroscience, 2014)
Many children with reading difficulties display phonological deficits and struggle to acquire nonlexical reading skills. However, not all children with reading difficulties have these problems, such as children with selective Letter Position Dyslexia (LPD), who make excessive migration errors (such as reading slime as ‘smile’). Previous research has explored three possible loci for the deficit – the phonological output buffer, the orthographic input lexicon, and the orthographic-visual analysis stage of reading. While there is compelling evidence against a phonological output buffer and orthographic input lexicon deficit account of English LPD, the evidence in support of an orthographic-visual analysis deficit is currently limited. In this multiple single-case study with three English speaking children with developmental LPD we aimed to both replicate and extend previous findings regarding the locus of impairment in English LPD. First, we ruled out a phonological output buffer and an orthographic input lexicon deficit by administering tasks that directly assess phonological processing and lexical guessing. We then went on to directly assess whether or not children with LPD have an orthographic-visual analysis deficit by modifying two tasks that have previously been used to localize processing at this level: a same-different decision task and a nonword reading task. The results from these tasks indicate that LPD is most likely caused by a deficit specific to the coding of letter positions at the orthographic-visual analysis stage of reading. These findings provide further evidence for the heterogeneity of dyslexia and its underlying causes.